Customer Choice and Preference on Food Deliver Apps Over Traditional Food Retailers in Kathmandu Valley - Mahato, Niraj (Nepalese Journal of Economics, 2025)
This study analyzed the customer choice and preference on food delivery apps over traditional food retailers in Kathmandu valley. The dependent variable is customer preference. Similarly, the selected independent variables are price, customer service, food quality, user friendly app, and delivery time. The primary source of data is used to assess the opinions of the respondents regarding the price, customer service, food quality, user friendly app, and delivery time in online food delivery apps. The study is based on primary data of 101 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of customer choice and preference on food delivery apps over traditional food retailers in Kathmandu valley. The study showed that price is negatively correlated to customer preference. It indicates that higher the price, lower will be the customer preference. Similarly, customer service is positively correlated to customer preference. It indicates that better the customer service, better will be the customer preference. Likewise, food quality is positively correlated to customer preference. It indicates that higher the food quality, better will be the customer preference. Further, user friendly app is positively correlated to customer preference. It indicates that better the user friendly app, better will be the customer preference. Moreover, delivery time is positively correlated to customer preference. It indicates that better the delivery time, better will be the customer preference.